Determinants of mental health in college students from Lima and Huanuco - Chau, Cecilia (2017)
The aim of this study was to identify the psychological variables that predict the mental health in a sample of 1, 024 students from Lima and Huánuco. For this purpose, the following scales were used: General Self-efficacy, Coping Estimation Inventory (COPE 60), Academic Experiences Questionnaire (QVA-r), Perceived Stress Scale (PSS) and SF36 questionnaire.Results showed that perceived stress, the avoidant coping, the interpersonal area and study center predict mental health. The mediation analysis revealed that stress mediates the relation between the avoidant coping and the mental health. These findings of this  research may contribute to the development of programs to improve the mental health in college students.